The Effect Of Profitability, Liquidity, Solvability, Sales Growth And Firm Size On Financial Distress In Mining Sector Listed On The Indonesia Stock Exchange - Clara Taniva (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to analyze the influence of profitability, liquidity, solvency, sales growth, and firm size on potential financial distress in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. Financial distress is defined as a condition in which a company experiences financial difficulties that could potentially lead to bankruptcy if not addressed immediately. This study uses a quantitative method with secondary data obtained from the annual financial statements of mining sector companies. Financial distress was measured using the Altman Z-Score method, while data analysis was carried out by multiple linear regression. This study examines the influence of five independent variables: profitability, liquidity, solvency, sales growth, and firm size on financial distress.The conclusion of this study is that financial factors such as profitability, liquidity, solvency, and company size are important indicators in predicting potential financial distress in the mining sector. This result is expected to be a reference for company management and investors in making strategic decisions to manage financial risks and mitigate potential financial distress